The crisis in American banking - White, Lawrence H. (Political economy of the Austrian school., 1993)
The U.S. banking system, its regulation and deregulation, and especially its deposit guarantees, continue to pose complex problems. The Crisis in American Banking offers six original perspectives on this continuing crisis, drawing from modern Austrian economics and from public choice theories that have seldom been applied to contemporary banking troubles. The contributors suggest that political regulation has seriously impaired the health of the banking industry. The authors consider long-term prospects for reform in the banking industry in light of the regulatory environment Much in the news.